Analisis Pengaruh Kurs, Harga Minyak Mentah Dunia, PDB Per Kapita Singapura Terhadap Volume Ekspor Minyak Mentah Indonesia Ke Singapura - Oloan F.s Tambunan; Elvis F Purba; Lastri Siahaan (Journal of Economic and Business, 2021)
The purpose of this study is toexplain the factors affecting the volumeIndonesia’s crude oil exports to Singapore,which include exchange rates, oil pricesworld crude and Singapore’s per capitagross domestic product (GDP) by volumeIndonesia’s crude oil exports to Singaporejointly or partial. The type of research inthis study is an explanatory research withquantitative approach, using secondarydata obtained from Indonesian CentralStatistics Agency, World Bank, andIndexmundi and analyzed with multiplelinear regression model using SPSS version22.00. The focus of this research is thevolume of Indonesia’s crude oil exports toSingapore 1994-2020.The data analysis used in thisresearch is statistical analysis multiplelinear regression using SPSS version 22.00.Test result F shows that the exchangerate, world crude oil prices, and grossdomestic product per Singapore. Partiallythere are two variables that have asignificant influence on the volume of oilexports Indonesian crude oil to Singapore, namely the exchange rate and world crudeoil prices which negative effect, while grossdomestic product per capita is positive andnot significantly affect the volume ofIndonesia’s crude oil exports to Singapore. Keywords : Exchange Rates,World Crude Oil, Gross Domestic Product,Per Singapore Capita, Indonesian Crude OilExports Volume To Singapore